Konsep Upah (Ujrah) Jasa Fotografi Antara Pemilik Dan Fotografer Ditinjau Menurut Ekonomi Islam : (Studi Kasus Mandiri Fotografer Desa Purba Tua Kecamatan Barumun Kabupaten Padang Lawas) - Helmina Sari Pohan; H. Junda Harahap; Aminah Lubis (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The research results show that: (1) The concept of wages (ujrah) in the Islamic economic perspective seen from the perspective of the subject/actor in carrying out their work is in accordance with the Islamic economic perspective. Judging from the Mandiri object perspective, this photographer has met the basic requirements, namely being professional in carrying out his work and there is no element of fraud, then the concept of wages aims to improve the welfare of workers, so that the business is not just pursuing profit but is for the welfare of citizens based on a spirit of togetherness and humanity. Employers are instructed to treat workers like their own family whose needs must be met, because what is really emphasized is an attitude of ta'awun and not being harmed or harming other parties. This is driven by the understanding that the basic needs of people who lack or cannot afford it are the obligations of all workers, including entrepreneurs. (2) The concept of wages (Ujrah) for photography services between the owner and photographer in Purba Tua Village, Barumun District, Padang Lawas Regency is in accordance with the concept of ujrah and Sharia principles. because the terms and conditions for paying wages have been fulfilled. In running the Independent Photographer business, the owner and photographer both enter into a wage agreement (ujrah) and it is agreed at the beginning of the contract, the owner hands over the camera to the manager to operate the camera and the wages earned will be given according to the agreement, namely after expenses have been deducted. This has been agreed upon by both parties, even though it is only through an oral agreement. The owner handed over the camera out of trust.